Civic ekphrasis: Classical and contemporary description in the public-speaking classroom. Issue 3 (2nd July 2020) - Geraths, Cory
ABSTRACT: Courses: Public Speaking. Objectives: This unit aims to (1) illustrate the classical and contemporary utility of ekphrasis ("description") as a genre of civic communication; and (2) introduce students to essential skills in public speaking, including invention, arrangement, and, in particular, style